College student perceptions of preferential treatment of college athletes. Issue 3 (2nd September 2019) - Fuller, Rhema; Lawrence, S. Malia; Harrison, C. Keith; Eyanson, Jeff; Griffin, Whitney
ABSTRACT: Though the NCAA and its member institutions engage in efforts to address the negative perceptions of intercollegiate athletics, recent scandals surrounding college athletes might be undermining these efforts. Therefore, the purpose of the current study was to examine the perceptions that individuals held about intercollegiate athletics. Specifically, this study focused on the perception that college athletes receive preferential treatment, or athletic preference. Additionally, this study also sought to identify strategies for modifying or altering perceptions of athletic preference. Survey research design was used to elicit college students' ( n  = 382) perceptions related to athletic preference. Findings suggest that students believe college athletes receive academic, social, and financial preferences. Further, participants indicated that these perceptions can potentially be addressed if academics are increasingly emphasized and if students and athletes are treated equitably. Practical implications and recommendations for intercollegiate athletics professional are discussed.